2004
DOI: 10.1079/bjn20041171
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diet on behaviour and cognition in children

Abstract: Diet can affect cognitive ability and behaviour in children and adolescents. Nutrient composition and meal pattern can exert immediate or long-term, beneficial or adverse effects. Beneficial effects mainly result from the correction of poor nutritional status. For example, thiamin treatment reverses aggressiveness in thiamin-deficient adolescents. Deleterious behavioural effects have been suggested; for example, sucrose and additives were once suspected to induce hyperactivity, but these effects have not been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
202
0
14

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(223 citation statements)
references
References 51 publications
(49 reference statements)
7
202
0
14
Order By: Relevance
“…This rate of glucose metabolism in children remains elevated until 9-10 years of age, before it declines to the adult level by late adolescence (Chugani, 1998). Therefore, regular meals and continuous glucose supply (to provide the brain with the required glucose for its high metabolism) is more important in children than in adults (Bellisle, 2004). Accordingly, children are more prone to the adverse effect of overnight fasting, and breakfast is a very important meal to provide fuel to the brain in the morning (Bellisle, 2004).…”
Section: Breakfastmentioning
confidence: 99%
See 1 more Smart Citation
“…This rate of glucose metabolism in children remains elevated until 9-10 years of age, before it declines to the adult level by late adolescence (Chugani, 1998). Therefore, regular meals and continuous glucose supply (to provide the brain with the required glucose for its high metabolism) is more important in children than in adults (Bellisle, 2004). Accordingly, children are more prone to the adverse effect of overnight fasting, and breakfast is a very important meal to provide fuel to the brain in the morning (Bellisle, 2004).…”
Section: Breakfastmentioning
confidence: 99%
“…We next consider the more encompassing aspects of diet, which have emerged as researchers became more interested in diet as a comprehensive measurement. The most recent research trend in this area suggests a broader analysis of the role of nutrition in neurocognitive development, which we offer here in comparison to previous reviews (Black, 2003b;Bellisle, 2004;Stevenson, 2006;Georgieff, 2007;Benton, 2010a).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research demonstrated the deleterious effects (both immediate and long-term) of poorquality nutrition on health (eg, obesity, dental caries), 14 as well as on behavior and cognition in children. 15,16 Of additional concern is the prevalence of energy-dense and low-nutritive purchases just before children begin the school day.…”
Section: Figurementioning
confidence: 99%
“…Nearly one third (31.9%) of children are overweight or obese (Նthe 85th percentile of BMI for age) and 16.3% are obese (Նthe 95th percentile). 1 These rates are even higher among children of ethnic minorities who live in low socioeconomic environments, approximating 50% who are at least overweight and 25% who are obese.…”
mentioning
confidence: 99%
“…The long term health costs of an overweight population (Gibson 1997) outweigh those of smokers (King, 2009). Interest in children"s nutritional intake is also linked to concerns about the effect of food processing upon children"s development (Bellisle 2004) and upon their behaviour (Tuormaa 1994). Concern about the influence of diet upon children"s wellbeing is therefore wide ranging (Dalmenny et al 2003) The food industry is dominated by corporate retail giants (Mintel 2008)) the majority of domestic expenditure on food being transacted therein.…”
Section: Introductionmentioning
confidence: 99%